Urinary excretion of proteins in chromeplaters, exchromeplaters and referents. - Lindberg, Eva; Vesterberg, Olof (Scandinavian Journal of Work, Environment & Health, 1983)
Urinary excretion of proteins in chromeplaters, exchromeplaters and referents. Scand j work environ health 9 (1983) 505-510. beta 2-microglobulin was measured in the urine of 24 presently exposed chromeplaters, 27 previously exposed chromeplaters, and 37 referents. The concentration of beta 2-microglobulin and the number of ``elevated'' values (greater than 0.30 mg/l) was higher in the presently exposed group than in the referents. Within the presently exposed group there was a dose-effect relation between the concentration of hexavalent chromium in air and the number of elevated values of urinary beta 2-microglobulin. However, no difference between the previously exposed chromeplaters and the referents could be demonstrated regarding urinary beta 2-microglobulin. There were no indications that the exposure could raise the excretion of albumin in urine. The results seem to indicate an acute effect on the kidney tubules, which is reversible even in workers who have had a relatively high exposure to chromic acid.